SNGH16 regulates cell autophagy to promote Sorafenib Resistance through suppressing miR‐23b‐3p via sponging EGR1 in hepatocellular carcinoma. (23rd April 2020) - Jing, Zhao; Ye, Xiaoping; Ma, Xiaojie; Hu, Xiangrong; Yang, Wenjun; Shi, Junping; Chen, Gongying; Gong, Ling
Abstract: Objective: Tumor cells could acquire drug resistance through cell autophagy. This study aimed to explore the role of SNHG16 in sorafenib‐resistant HCC cells and its mechanism with miR‐23b‐3p. Methods: The sorafenib‐resistant Hep3B cell model was established. The SNHG16 and miR‐23b‐3p gene expressions were determined in normal HCC and sorafenib‐resistant HCC tissues. Detection of the expression of SNHG16 and miR‐23b‐3p and its respective correlation with survival rate were performed. Target genes to SNHG16 and miR‐23b‐3p were predicted, and verified by dual‐fluorescent reporter assay. The effects of SNHG16 and miR‐23b‐3p on SNHG16, miR‐23b‐3p, EGR1 expression, viability, apoptosis as well as LC3II/LC3 expression in Hep3B and Hep3B/So cells were detected by qRT‐PCR, CCK‐8, flow cytometry, and western blot. In in vivo studies, the NOD/SCID mice model was established to explore the effects of Hep3B and Hep3B/So cells with inhibited SNHG16 or miR‐23b‐3p on tumor size, EGR1 expression, and autophagy. Results: High SNHG16 expression in HCC‐resistant tissues and low miR‐23b‐3p expression in all HCC tissues were detected, and the two were negatively correlated. Low SNHG16 and high miR‐23b‐3p were related to a high survival rate of HCC patients. Moreover, SNHG16 overexpression promoted Hep3B/So cell viability and autophagy, suppressed apoptosis by inhibiting miR‐23b‐3p expression through up‐regulating EGR1, however, the effect of si‐SNHG16 was opposite. In in vivo studies, miR‐23b‐3p inhibitor suppressed the high sorafenib sensitivity in Hep3B/So cells caused by SNHG16 silencing through promoting viability, autophagy, and suppressing apoptosis. Conclusion: SNHG16 promotes Hep3B/So cell viability, autophagy, and inhibits apoptosis to maintain its resistance to sorafenib through regulating the expression of miR‐23b‐3p via sponging EGR1. Abstract : This study demonstrated the promoter role of SNHG16 played in regulating autophagy in Hep3B cells with sorafenib resistance, which further contribute to a stronger sorafenib resistance in Hep3B cells. Moreover, the above process implemented through regulating the expression of miR‐23b‐3p via sponging EGR1.